MENENTUKAN SAHAM YANG EFISIEN DENGAN MENGGUNAKAN METODE CAPITAL ASSET PRICING MODEL (CAPM) - LIADI, ELVINA; DHARMAWAN, KOMANG; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika, 2020)
CAPM has been well known as a method to select which stocks are efficient in a portfolio. The purpose of this study is to determine efficient stocks using CAPM method. Data used in this study are the monthly closing prices recorded from February 2016 to July 2018. The results of this study indicate that the CAPM is able to show efficient stocks with differences in the return and expected return of a positive or negative value of CAPM. In this study, it is found that AMAG.JK, ASBI.JK, ASJT.JK, ASMI.JK, ASRM.JK, PNIN.JK, VINS.JK, LPGI.JK, MREI.JK are efficient stocks while ABDA.JK, AHAP.JK, ASDM.JK are inefficient stocks